Facial affect recognition in first-episode psychosis is impaired but not associated with psychotic symptoms. Issue 9 (September 2022) - Larsson, Cornelia; Lee, Maria; Lundgren, Tobias; Erhardt, Sophie; Sellgren, Carl M.; Cervenka, Simon; Borg, Jacqueline; Bölte, Sven; Fatouros-Bergman, Helena
Abstract: Introduction: Social dysfunction is a key feature of psychotic disorders such as schizophrenia linked to disability. Less is known about social functioning in the early stages of the disorder and if there is an association to psychotic symptoms. Aims: Investigate if antipsychotic drug-naïve or briefly medicated individuals with first-episode psychosis (FEP), have impaired facial affect recognition (FAR) compared to control participants and if psychotic symptoms are associated with the FAR ability. Method: Individuals with FEP (n = 67) and control participants (n = 51) performed a computer-aided FAR task on basic emotions. Psychotic symptoms were assessed with the Positive and Negative Syndrome Scale (PANSS). Group performances were compared using age and gender as covariates. The associations between FAR and performance on the subscales of PANSS were analyzed. Results: Compared to control participants, individuals with FEP were impaired in general FAR (Beta = -2.04 [95 % conf: -3.75/-1.62], p < 0.001) and FAR of negative emotions (Beta = -1.74 [95 % conf: -3.08/-1.22], p < 0.001), driven by difficulties in recognition of anger and disgust. In both groups, there was a pattern of mistaking negative emotions for other negative emotions. There were no significant group differences in FAR of happiness. No significant associations between FAR and psychotic symptoms were observed. Discussion: The results indicate that FAR, an underlying mechanism of social functioning is impaired early in the course of psychotic disorders. Current findings do not support the hypothesis that misinterpretation of facial expressions in individuals with FEP underlies or contributes to symptoms of psychosis. Highlights: Impaired affect recognition (FAR) present already in first episode psychosis (FEP). Preserved FAR of happiness found in individuals with FEP. Individuals with FEP mainly have impaired FAR of negative affects. Both FEP and controls mainly mistook negative affects for other negative affects. Psychotic symptoms are not associated with FAR in individuals with FEP. Abstract : First episode psychosis (FEP), Facial affect recognition (FAR), Cognition, Emotion recognition, Social cognition, Antipsychotic drug-naïve.